Scale-Up Strategy of Village-Owned Enterprises in Sigi District: Institutional Transformation Towards Digitalization - Umar Umar; Cahyaning Raheni; Nursalim Nursalim; Rizkiani Iskandar; Tovan Tovan; Mutmainah Mutmainah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the strategy for improving Village-Owned Enterprises in Sigi Regency. This research aims to develop strategies through institutional transformation towards digitalization. This type of research is descriptive qualitative which aims to explore information by investigating events on the object of research through observation, interviews, and focus group discussions. The results show that out of 153 Village-Owned Enterprises in Sigi Regency, only 17 are productive out of 77 that are still active, so there is a need to increase human resource capacity and develop digital infrastructure through multi-party collaboration. The Asset-Based Community Development (ABCD) approach has an impact on the development of Village-Owned Enterprises.